Case report: A 51-year-old diabetic patient with primary bilateral macronodular adrenal hyperplasia and primary hyperparathyroidism - Zhong, Yuan; Zhang, Tao; Li, Fan; Chen, Yong; Tong, Liwei; Xia, Chenxi; Wei, Dong (Frontiers in Endocrinology, 2024)
A 51-year-old female patient with diabetes mellitus and hypertension, exhibiting poor control of blood sugar and blood pressure, was unexpectedly found to have multiple large adrenal nodules, excessive cortisol secretion, and adrenocorticotropic hormone inhibition. Cortisol levels remained unresponsive to both low-dose and high-dose dexamethasone tests, leading to a diagnosis of primary bilateral macronodular adrenal hyperplasia. Concurrently, elevated blood calcium and parathyroid hormone levels, along with 99mTc-methoxyisobutyl isonitrile (99mTc-MIBI) imaging revealing increased 99mTc-MIBI uptake in the right inferior parathyroid gland, suggest the consideration of primary hyperparathyroidism. This case is presented in light of the uncommon clinical coexistence of primary bilateral macronodular adrenal hyperplasia and primary hyperparathyroidism.